2019
DOI: 10.1158/1078-0432.ccr-19-0510
|View full text |Cite
|
Sign up to set email alerts
|

TRIB3 Stabilizes High TWIST1 Expression to Promote Rapid APL Progression and ATRA Resistance

Abstract: Purpose: The resistance to differentiation therapy and early death caused by fatal bleeding endangers the health of a significant proportion of patients with acute promyelocytic leukemia (APL). This study aims to investigate the molecular mechanisms of all-trans retinoic acid (ATRA) resistance and uncover new potential therapeutic strategies to block the rapid progression of early death. Experimental Design: The important role of TWIST1 in APL leukemogenesis was first determined by gain-and lossof-function ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
(55 reference statements)
1
20
0
Order By: Relevance
“…J. Xu's group reported recently that TWIST1 is involved in arsenic trioxide resistance in acute promyelocytic leukemia (APL) patients. 11 This observation and ours, taken together, suggest possible association of aberrant TWIST1 expression with therapeutic failure in hematopoietic malignancies. Our detailed analysis reveals that TWIST1 can interact with both wild-type and mutated DNMT3a and disrupt DNMT3a/TWIST1 interaction can block induction of DAC resistance.…”
supporting
confidence: 60%
“…J. Xu's group reported recently that TWIST1 is involved in arsenic trioxide resistance in acute promyelocytic leukemia (APL) patients. 11 This observation and ours, taken together, suggest possible association of aberrant TWIST1 expression with therapeutic failure in hematopoietic malignancies. Our detailed analysis reveals that TWIST1 can interact with both wild-type and mutated DNMT3a and disrupt DNMT3a/TWIST1 interaction can block induction of DAC resistance.…”
supporting
confidence: 60%
“…Strikingly, RBCK1‐TRIB3 was identified in pre‐APL (collected at 19 October 2018) but not overt‐APL sample (collected at 22 January 2020/1/22) (Tables S1 and S2), and this result was also confirmed by RT‐PCR (primers: forward 5′‐TATGGCTTCCCACCAGTCTT‐3′, reverse 5′‐CTTCGAGCTCGTTTCTGGAC‐3′) (Figure 1L). It has been reported that TRIB3 promoted APL progression via stabilizing PML‐RARA 4,5 . In RBCK1‐TRIB3 , the breakpoint located at the exon 4 of RBCK1 and the exon 2 of TRIB3 (Figure 1M).…”
Section: Resultsmentioning
confidence: 89%
“…It has been reported that TRIB3 promoted APL progression via stabilizing PML-RARA. 4,5 In RBCK1-TRIB3, the breakpoint located at the exon 4 of RBCK1 and the exon 2 of TRIB3 (Figure 1M). Due to the out-frame fusion, RBCK1-TRIB3 was premature terminated and the TRIB3 portion was completely lost.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicated that the decreased protein expression of TRAF6 in lung fibroblasts during PF progression might result from an alteration in its protein stability. Our group, along with others, has reported that TRIB3, a well-known stress sensor, is involved in regulating the stability of various proteins in the pathogenesis of chronic diseases ( Lin et al, 2019 ; Yu J. M. et al, 2019 ; Liu S. et al, 2021 ). We then reasoned that TRIB3 might participate in regulating the altered protein expression of TRAF6.…”
Section: Resultsmentioning
confidence: 89%
“…TRIB3, a stress sensor, is involved in the pathogenesis of various diseases, including obesity, diabetes, and tumors ( Du et al, 2003 ; Oberkofler et al, 2010 ; Lin et al, 2019 ). Accumulating evidence has widely demonstrated that TRIB3 plays a vital role in organ fibrogenesis ( Wang et al, 2014 ; Tomcik et al, 2016 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%